Rethinking the potential and necessity of drug delivery systems in neovascular age-related macular degeneration therapy - Huang, Xi; Zhang, Li; Fu, Yanyan; Zhang, Meixia; Yang, Qian; Peng, Jinrong (Frontiers in Bioengineering and Biotechnology, 2023)
Age-related macular degeneration (AMD) is the predominant threat to human vision and ultimately results in blindness. With the increase in the aging population, it has become a more crucial issue to human health. AMD is a multifactorial disease with the unique feature of uncontrollable angiogenesis during initiation and progression. Although increasing evidence indicates that AMD is largely hereditary, the predominant efficient treatment is antiangiogenesis, which mainly involves VEGF and HIF- as therapeutic targets. The repeated administration of this treatment over the long term, generally through intravitreal injection, has called for the introduction of long-term drug delivery systems, which are expected to be achieved by biomaterials. However, the clinical results of the port delivery system indicate that the optimization of medical devices toward prolonging the activities of therapeutic biologics in AMD therapy seems more promising. These results indicate that we should rethink the possibility and potential of biomaterials as drug delivery systems in achieving long-term, sustained inhibition of angiogenesis in AMD therapy. In this review, the etiology, categorization, risk factors, pathogenesis, and current clinical treatments of AMD are briefly introduced. Next, the development status of long-term drug delivery systems is discussed, and the drawbacks and shortages of these systems are emphasized. By comprehensively considering the pathological aspect and the recent application of drug delivery systems in AMD therapy, we hope to find a better solution for the further development of long-term therapeutic strategies for AMD.